2019
DOI: 10.3390/app9122437
|View full text |Cite
|
Sign up to set email alerts
|

Transporting and Storing High-Level Nuclear Waste in the U.S.—Insights from a Mathematical Model

Abstract: The nuclear industry in the United States of America has accumulated about 70,000 metric tons of high-level nuclear waste over the past decades; at present, this waste is temporarily stored close to the nuclear power plants. The industry and the Department of Energy are now facing two related challenges: (i) will a permanent geological repository, e.g., Yucca Mountain, become available in the future, and if yes, when?; (ii) should the high-level waste be transported to interim storage facilities in the meantim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…These actinide-loaded crystalline waste forms would then be permanently disposed of in either a mined geologic repository or deep borehole. 32,[45][46][47] However, any potential immobilization matrix disposed of in either of the geologic disposal strategies will encounter elevated temperatures, ranged between 70 °C and 350 °C, as a result of the radiogenic decay heat mainly generated by short lived radionuclides. [48][49][50][51][52] Thus, a fundamental understanding of the thermal behavior of such solid solution is needed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These actinide-loaded crystalline waste forms would then be permanently disposed of in either a mined geologic repository or deep borehole. 32,[45][46][47] However, any potential immobilization matrix disposed of in either of the geologic disposal strategies will encounter elevated temperatures, ranged between 70 °C and 350 °C, as a result of the radiogenic decay heat mainly generated by short lived radionuclides. [48][49][50][51][52] Thus, a fundamental understanding of the thermal behavior of such solid solution is needed.…”
Section: Introductionmentioning
confidence: 99%
“…While it has been shown that a zircon doped with 10 wt % 239 Pu would become fully amorphous after only 1400 years, preliminary calculations have shown that very little Pu would be ultimately released over a 500 000 year time span due to the relatively short half-life of 239 Pu as well as the low solubility of amorphous zircon. , Thus, as uranium is the main component of spent nuclear fuel ,, and cerium constitutes a useful surrogate for plutonium, these minerals are also representative of how long-lived actinides will behave when incorporated into the zircon structure. These actinide-loaded crystalline waste forms would then be permanently disposed of in either a mined geologic repository or deep borehole. , …”
Section: Introductionmentioning
confidence: 99%
“…Currently, many countries are investigating solid matrices in order to immobilize the actinides prior to permanent disposal 2 . The immobilization step is typically accomplished either by vitrification or cementation, while the permanent disposal is completed either by a deep-mined geologic repository or deep bore-hole [3][4][5] . The main concern with this strategy, is the long-term safety associated with a disposal system's integrity on time scales that range from thousands to hundreds of thousands of years 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Currently, many countries are investigating solid matrices to immobilize the actinides prior to permanent disposal . The immobilization step is typically accomplished by either vitrification or cementation, while permanent disposal is completed by either placement in a deep-mined geological repository or a deep bore hole. The main concern with this strategy is the long-term safety associated with a disposal system’s integrity on time scales that range from thousands to hundreds of thousands of years . The structural and chemical stability of ceramics has been ascertained by studies of minerals, such as garnet, pyrochlore, zircon, zirconolite, apatite, and monazite, which are all known to be able to incorporate Th and U over geologic time scales that stretch well beyond 1 million years .…”
Section: Introductionmentioning
confidence: 99%
“…Currently, many countries are investigating ceramic waste forms to immobilize actinides prior to final disposal (Orlova and Ojovan 2019). If a zircon-type waste form is used, the immobilization step would be accomplished by incorporating the actinides into its crystal structure and then placing the ceramic waste form in either a deep-mined geologic repository or deep bore-hole (Weber et al 2009(Weber et al , 2019Goel et al 2019;Wegel et al 2019). As zircon has been shown to be a durable mineral able to immobilize Th and U over geologic time scales that stretches well beyond hundreds of million years (White 2015), it addresses the concerns for the long-term safety associated with the integrity of a disposal system on time scales that range from thousands to tens of hundreds of thousands of years .…”
Section: Introductionmentioning
confidence: 99%